[GRADUAÇÃO | MONOGRAFIA] DO FEITIÇO A BANALIZAÇÃO DO MAL: UMA RELEITURA DE COMO A PROPAGANDA NAZISTA INFLUENCIOU A ASCENSÃO DO ANTISSEMITISMO NA SEGUNDA GUERRA MUNDIAL - MELLO, MARIA EDUARDA ROCHA E (Portal de Trabalhos Acadêmicos, 2019)
Propaganda can be defined as a broadcast tool of ideological messages in order to influence the behavior of society. Advertising as a tool that aims to make known and desired brands, with eminent commercial appeal . In the contemporary political marketing there is a clear fusion of ideological content and advertising format in order to build identities of political brands, sum of professed ideologies, actions taken and effective communication with voters - users ( citizens). This monograph will be addressed concepts and features present in Nazi propaganda as a way to spread the dominant ideology , distinguishing communication as a complex shape relationship between state and citizens, in order to consolidate the power of hegemonic groups on the social behavior guidelines population.